Pengukuran Kinerja Keuangan Melalui Penggunaan Analisis Rasio Keuangan pada PT Kalbe Farma Tbk - Sari, Lusiana Fatika; Bahri, Ahmad Syaiful; Wibowo, Luthfi Yoga Hendy (Fakultas Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2023)
The purpose of this research is to carry out a descriptive analysis of the procedure for measuring financial performance which is reviewed based on financial ratio analysis using financial ratios in the form of liquidity ratios, solvency ratios, activity ratios, and profitability ratios. The object chosen in this study is PT Kalbe Farma Tbk, the financial statements have been uploaded to the Indonesia Stock Exchange (IDX). The research approach used in this study is a qualitative approach. The focus of this research is the financial statements of the company PT Kalbe Farma Tbk, which are balance sheets and income statements for the 2020-2022 period. The source of data used in research is secondary data. The data collection technique used in this research is a literature study. The data analysis used in this research is descriptive analysis. The results of the financial ratio analysis consisting of liquidity ratios, solvency ratios, activity ratios, and profitability ratios for the 2020-2022 period show that the financial performance of PT Kalbe Farma Tbk is in fairly good condition.